PENDAMPINGAN PENGELOLAAN KEUANGAN BERBASIS APLIKASI LAMIKRO DAN IMPLEMENTASI HAK KEKAYAAN INTELEKTUAL - Perdanawati, Luh Putu Virra Indah; Seputra, Anak Agung Putu Oka (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
Business actors still use manually compiled financial reports, on the other hand business actors are increasingly aware of the importance of a legal approach, especially related to copyrights to register Intellectual Property Rights (IPR) in order to legally protect businesses. The purpose of this community service activity was to provide assistance in compiling standardized financial reports and to increase awareness of the risks of not having an IPR. This activity was carried out in several stages, namely planning and preparation, direct observation, interviews, socialization of the use of applications and practices, as well as monitoring and evaluation. Partner in this PKM activity was Yande Shell Coconut Shell Craft Businesses located in Banjarangkan District, Klungkung Regency, Bali Province. The community service implementation team consisted of two lecturers and 22 students. The results of the implementation of the activities showed t an increase in quality in the presentation of financial reports based on accounting standards and protection of products through IPR which protects these products from product imitators and have economic value.